Explaining Privatization Failure: The Vice of Sweet Carrots and Hard Sticks. (March 2019) - Zullo, Roland
Why does contracting underperform in the production of publicly financed goods? Producers for private markets survive through marketism, defined as the strategic exclusion of segments of a community, whereas producers of publicly financed goods are pressured to be inclusive. Inclusivity is achieved through universalism, an operational mode with three requisites: (1) a workforce with lateral competency to respond to contingencies, (2) interfunction asset sharing and coordination, and (3) an environment that protects professional discretion. Universalism and marketism are divergent strategies, and public-private contracts cannot cost-effectively resolve their incongruities. JEL Classification: L330, H410, P260